Procedimentos e implicações na elaboração de um teste de sentenças no ruído para o português brasileiro - Paz-Oliveira, Andréa (2017)
Introduction: basic audiological field evaluation, syllables and words have been used to measure the individual's auditory performance in speech recognition tasks. Increasingly, however, increases the number of searches that claim that the test for the recognition of sentences in noise is the best instrument to evaluate the communication in your daily life. This way, elaborate sentences in noise tests is of extreme importance to clinical practice. Objective: Develop a material of sentences in noise for Brazilian Portuguese. Method: to achieve the objective of this research, we developed a study of prospective, descriptive, exploratory, quantitative and qualitative. The survey was conducted in three experiments: 1: Material development process development of judgments and application without noise in subjects without hearing loss. 2: examining the influence of different signal-to-noise ratios on the performance of subjects visually-listeners 3: analyze the performance of subjects visually-listeners in the application of sentences with selected noise in experiment 2. Results: 23 lists were made with six sentences each (total of 138 sentences) phonetically balanced, with five words each target, and content is not predictable. From the application, in the silence, in subjects without hearing loss, the equivalent lists with each other were selected and applied with noise to analyze which background noise should be inserted in the search. The noises were selected 0dB, -5 dB,-10dB, + 5dB, + 10dB to + 15dB. The relationship signal-noise 0dB,-5dB and -10 the proportion of hits is greater in mixed lists and other signal-to-noise ratios there is no difference between the mixed lists or (+5, +10, +15). Conclusion: the sentences developed are phonetically balanced, equivalent to each other, and rapid facies are applied